Otto Herbert Arnold Schmitt (1913-1998), a pioneer (an overview of Schmitt's scientific production). - Valentinuzzi, M.E (IEEE Engineering in medicine and biology magazine)
Otto Schmitt was a prolific intellectual creator with over 60 patents and more than 300 scientific and technical publications produced during his lifespan. In addition, he left an enormous amount of manuscripts, letters, and equipment of different types. The objective here is to give an overview of his published production trying to separate out and group the many subjects he dealt with assessing also the impact some of them had. There are an important number of papers in physiology, which in turn subdivide in electrophysiology, neuroscience, and electrocardiology. Chronobiology was for him a matter of concern, too. A few belong to biomedical engineering at large, including clinical engineering. Electromagnetic fields called his interest during a period of his life and, curiously enough, bioinstrumentation, which accounted for only about 3% of his whole production, was the area of highest impact, displaying his most known and still used contributions: the now called Schmitt trigger, the differential amplifier and the radio frequency (RF) isolating unit. He was collaborator of Nobel Class researchers, and he could be considered as a member of such class. No doubt, he was a pioneer in biomedical engineering.